A feasibility study evaluating the uptake, effectiveness and acceptability of routine screening of pregnant migrants for latent tuberculosis infection in antenatal care: a research protocol. Issue 4 (4th April 2022) - Rahman, A; Thangaratinam, Shakila; Copas, Andrew; Zenner, D; White, Peter J; Griffiths, Chris; Abubakar, Ibrahim; McCourt, Christine; Kunst, Heinke
Abstract : Introduction: Globally, tuberculosis (TB) is a leading cause of death in women of reproductive age and there is high risk of reactivation of latent tuberculosis infection (LTBI) in pregnancy. The uptake of routine screening of migrants for LTBI in the UK in primary care is low. Antenatal care is a novel setting which could improve uptake and can lend insight into the feasibility and acceptability of offering opt-out screening for LTBI. Methods and analysis: This is an observational feasibility study with a nested qualitative component. The setting will be the antenatal clinics in three hospitals in East London, UK . Inclusion criteria are pregnant migrant women aged 16–35 years attending antenatal clinics who are from countries with a TB incidence of greater than 150/100 000 including sub-Saharan Africa, and who have been in the UK for less than 5 years. Participants will be offered LTBI screening with an opt-out interferon gamma release assay blood test, and be invited to complete a questionnaire. Both participants and healthcare providers will be invited to participate in semistructured interviews or focus groups to evaluate understanding, feasibility and acceptability of routine opt-out LTBI screening. The primary analysis will focus on estimating the uptake of the screening programme along with the corresponding 95% CI. Secondary analysis will focus on estimating the test positivity. Qualitative analysis will evaluate the acceptability of offering routine opt-out LTBI screening to participants and healthcare providers. Ethics and dissemination: The study has received the following approvals: Health Research Authority (IRAS 247388) and National Health Service Ethics Committee (19/LO/0557). The results will be made available locally to antenatal clinics and primary care physicians, nationally to NHS England and Public Health England and internationally through conferences and journals. Trial registration number: NCT04098341 .